Slip distribution and block rotation of the Indo-South China region inferred from GNSS analyses. (1st August 2022) - Xu, Bin-Bin; Wang, Yang; Zhang, Zhu-Qi; Yan, Yong-Gang; He, Xiao-Hui; Hao, Ming; Wang, Wei-Tao; Li, Zhi-Gang; Zhang, Yi-Peng; Tian, Qing-Ying; Wang, Yue-Jun; Zheng, Wen-Jun; et al.
Graphical abstract: Highlights: The relative motion between India and South China is accommodated by regional right-lateral shearing. The newly formed Shan Plateau Shear Zone at depth drives the sinistral slip of ENE-trending faults and the upper crust clockwise rotation. The pattern of Indo-South China Region results from wide dextral shear, clockwise rotation around the Eastern Himalayan Syntaxis. Abstract: Indo-South China lying between the Indian Plate and the rigid South China Block is characterized by intense crustal deformation with severe seismic hazards. How deformation is partitioned through slip on various structural features provides key insights into understanding the regional geodynamic processes. Based on the up-to-date GPS velocity data together with the existing active tectonic, seismological, and geophysical data, we find that the relative motion between India and South China is mainly accommodated by two parts: ∼47 mm/yr dextral slip and 15–18 mm/yr contraction to the west of the Shan Plateau, and ∼ 10 mm/yr sinistral slip and ∼ 10 mm/yr extension to the east of it. The Burmese Range takes up ∼ 22 mm/yr dextral slip and 10–13 mm/yr contraction, while the Sagaing Fault accommodates ∼ 18 mm/yr dextral slip and 5–6 mm/yr contraction. The Shan Plateau Shear Zone absorbs ∼ 8 mm/yr dextral slip and 5–6 mm/yr extension. The Chuandian Terrane from east of the Red River Fault to the Xiaojiang Fault manifests 8–10 mm/yr sinistral slip and 5–6 mm/yr extension. The block motion inversion reveals that the clockwise rotation and deformation are caused by the northeastward motion of the India Plate and the clockwise lithospheric flow around the Eastern Himalayan Syntaxis. The Shan Plateau Shear Zone may be a newly formed dextral shear zone at depth of the middle and lower crust, driving the sinistral slip and extension along the ENE-trending faults in upper crustal level. The Shan Plateau Shear Zone might have replaced the Red River Fault as the western boundary to cause the southeastward coherent movement of the Chuandian Terrane. The complex pattern of active tectonic deformation in the region results from interactions among hyper-oblique subduction beneath the Burmese Range, clockwise rotation of lithospheric material around the Eastern Himalayan Syntaxis, and the apparently rigid Sundaland Block separating the two systems in between.